An annotated catalogue of the type material of Elateroidea Leach, 1815 (Coleoptera) deposited in the Coleoptera collection of the Museum of Zoology of the University of São Paulo, Brazil - Ferreira, Vinicius De Souza (Zootaxa, 2015)
The Museum of Zoology of the University of São Paulo (MZSP) houses one of the most important Coleoptera collections of Brazil and Neotropical Region with nearly 900,000 adult mounted material and about 1,500,000 specimens to be mounted. The superfamily Elateroidea Leach, 1815 (including Cantharoidea) comprises about 24,077 described species in 17 families. The MZSP owns type material of Brachypsectridae LeConte & Horn, 1883, Cantharidae, 1856 (1815), Cerophytidae Latreille, 1834, Elateridae Leach 1815, Eucnemidae Eschscholtz, 1829, Lampyridae Rafinesque, 1815, Lycidae Laporte, 1836, Phengodidae LeConte, 1861 and Rhinorhipidae Lawrence, 1988. This catalogue includes type material of 166 species distributed in 69 genera. Among 1,223 type specimens, are 86 holotypes, 1,133 paratypes, 2 allotypes, 1 lectotype and 1 paralectotype.